Colossians: an introduction and study guide : authorship, rhetoric, and code - Anderson, Janice Capel (T & T Clark study guides to the New Testament, 2020)
Stories of Colossians and authorship -- Rhetoric and opposition -- The household code, ethics, and interpretation.